'If We be Dead with Christ'1: Christian Visualisations of Death. (August 2016) - Quash, Ben
Sixteenth-century Florentines have left us a visual legacy showing them capable of imagining even the executions of criminals as redemptive deaths, with artistic representations of Christ's own death and the martyrdoms of saints serving such interpretations. This article will look in detail at one such case, before asking whether there might be analogies to this construction of executions as 'good deaths' where other, less obviously dramatic kinds of dying are concerned. The comfort that Christian art about dying can give to the dying is its ability to help them imagine their union with Christ in whatever death they must undergo. On the premise that art about dying can be of fundamental assistance to the art of dying, the article proposes examples of works of Christian art that may address the 'long dying' so common in our own medically advanced societies, thereby proclaiming the reach and inclusiveness of the hope of redemption.